The Impact of Financial Accountability, Internal Control and Government Expenditure on Social Welfare - Baries Ferryono; M. Pudjihardjo; Ferry Prasetyia (Journal of International Conference Proceedings (JICP), 2022)
One of the goals of the Indonesia is social welfare. However, there are still Indonesian people who suffer for living. The local government expenditure, which is expected to encourage welfare, still hasn`t show satisfactory results. This study aims to determine the impact of financial accountability, internal control and government expenditure on social welfare. This research was conducted in 508 districts/cities in Indonesia within period between 2015-2019. The results indicate that financial accountability has various effects on welfare. Only the unqualified opinion has a significant effect on all welfare indicators. The audit findings were not proven to have a significant effect on welfare. The results also indicate that internal control has a significant influence on all welfare indicators. The higher the internal audit capability and the internal control system maturity level, the greater the impact on promoting welfare. Government expenditure, in aggregate, has a significant effect on most welfare indicators. The results of this study further strengthen the role of internal control to promote welfare. Therefore, it is important that the local government considered improving the internal audit capability and the internal control system. Keyword: Accountability, Government Expenditure, Internal Audit Capability, Internal Control System, Welfare